Toponymy of Villages in Purwokerto Timur District as a Local History Learning Resource - Agung, Rendi Marta; Satata, Dian Bagus Mitraeka; Wulandari, Nuryuana Dwi (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This study aims to determine 1) the history of Banyumas Regency; 2) The meaning of the toponymy of the sub-districts in East Purwokerto District and 3) The contribution of toponymy in education. This study uses the Literature Study method which is strengthened by interviews. The results of this study are 1) Banyumas Regency was originally one of the areas under the rule of Ancient Mataram which later developed into a district; 2) The toponymy of six sub-districts in East Purwokerto District is related to the Ancient Mataram kingdom and the vegetation around the area; 3) toponymy has a very close relationship with local history so that it can realize the independent curriculum with a focus on learning related to local locality and local wisdom.